2008
DOI: 10.1002/cphc.200800563
|View full text |Cite
|
Sign up to set email alerts
|

Surface‐Enhanced Raman Scattering from a Single Nanoparticle–Plane Junction*

Abstract: Since the first observation of single-molecule level surface-enhanced Raman scattering (SERS) [1][2][3] from randomly aggregated noble metal nanoparticles, much effort has been made to understand the electromagnetic and chemical mechanisms behind the observed enhancement, and to fabricate structures that exhibit strong and reproducible SERS activities.It is widely accepted [4,5] that the locally enhanced electromagnetic (EM) field formed between the noble metal nanoparticles is mostly responsible for the stron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
82
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(88 citation statements)
references
References 36 publications
5
82
0
1
Order By: Relevance
“…These facts imply that the strong SERS effects depend much more on the nanogaps in the nano-networks than on the nano-junctions between the film and the large individual gold nanoparticles. In our previous work [38], purely network-like nanoporous gold films assembled at the air-water interface also showed very strong SERS activity using Py probe molecules, confirming that nanogaps in nano-networks play the key role in the huge enhancement [4,39,40].…”
Section: Resultssupporting
confidence: 52%
“…These facts imply that the strong SERS effects depend much more on the nanogaps in the nano-networks than on the nano-junctions between the film and the large individual gold nanoparticles. In our previous work [38], purely network-like nanoporous gold films assembled at the air-water interface also showed very strong SERS activity using Py probe molecules, confirming that nanogaps in nano-networks play the key role in the huge enhancement [4,39,40].…”
Section: Resultssupporting
confidence: 52%
“…In comparison to the EF values in Figure 1c, the system with the largest EF was most sensitive to d . For both dielectric and metal substrates, the interaction of the plasmon modes of the nanoparticle with the substrate will decrease as the gap distance between the nanoparticle and the substrate increases, [22,23] This data suggests that the near-fields of the Ag nanocube were affected by its supporting substrate, resulting in an additional enhancement in its SERS and formation of hot spots.…”
mentioning
confidence: 99%
“…Pioneering experimental studies demonstrated that such NP-plane junctions are capable of providing remarkably reproducible SERS-active compared with the NP-NP junctions [24]. Moreover, due to the coupling between the LSP of the nanoparticle and the propagating surface plasmon (PSP) formed on the conducting surface, electromagnetic enhancement shows more advantageous than that of a glass substrate, in which only LSP mode is present.…”
Section: Introductionmentioning
confidence: 98%
“…An alternative junction is created in a nanoparticle-plane gap-mode system, in which one of the NPs is replaced by a smooth metal film [19][20][21][22][23][24][25][26][27]. Pioneering experimental studies demonstrated that such NP-plane junctions are capable of providing remarkably reproducible SERS-active compared with the NP-NP junctions [24].…”
Section: Introductionmentioning
confidence: 98%